Controversies in Management of the Nasal Airway and Sleep Disorders. (2nd September 2014) - Woodson, B. Tucker; Rotenberg, Brian; Soose, Ryan J.; Friedman, Michael; Ishman, Stacey L.
Abstract : Program Description: Surgical and medical management of the nasal airway has traditionally not been considered primary indication for sleep disorders' treatment. Controversy exists over nasal surgery as primary treatment of snoring and sleep apnea. Algorithms to manage sleep‐disordered breathing often ignore or dismiss the nasal airway. This miniseminar addresses the following controversies: (1) Is the nasal airway an important contributor to sleep disorders? (2) Does nasal surgery affect sleep? (3) Does nasal treatment affect the use of continuous positive airway pressure? and (4) What is the role and documented effect of nasal surgery sleep apnea treatment in adults and children? Educational Objectives: (1) Justify using appropriate evidence‐based outcome metrics of medical and surgical treatment of the nose for specific sleep‐related breathing disorders. (2) Compare medical outcomes of sleep apnea treatment with and without treatment of nasal obstruction. (3) Describe potential differences and obstacles in treating nasal obstruction using traditional definitions versus treating it as a spectrum of sleep disordered breathing.